Near-infrared optical imaging for intraoperative identification and assessment of parathyroid glands - Jie Kang; Ziyang Ye; Chao Yan; Bobo Gu (Journal of Innovative Optical Health Sciences)
Accurate identification and viability assessment of the parathyroid glands (PGs) are critical when performing thyroid and parathyroid surgeries. Traditional visual inspection-based intraoperative methods suffer from subjectivity and uncertainty. Near-infrared (NIR) imaging methods, including NIR autofluorescence (NIRAF) imaging and indocyanine green fluorescence imaging (ICGFI), have emerged as promising and reliable techniques for intraoperative PG identification and assessment. Here, the principles and clinical performance of NIR imaging methods were comprehensively reviewed.